2018
DOI: 10.20546/ijcmas.2018.710.101
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming with Salicylic Acid Improves Germination and Seedling Growth of Rice (Oryza sativa L.) under PEG-6000 Induced Water Stress

Abstract: Seed germination and seedling establishment are most vital stages in plant growth cycle, playing major role in determining the final density of plants. In drought prone areas, poor seed germination and seedling emergence are the major problems. Seed priming is known to improve germination and seedling emergence under different environmental stresses. Salicylic acid (SA) also plays a major role in regulation of many physiological processes e.g. growth, development, ion absorption and germination of plants. An e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…2). Similar results were found in the experiments of Hanan (2007), Singh and Usha (2003) and Shatpathy et al (2018). With the SFW value of 0.437 gm and SDW value 0.35 gm.…”
Section: Seedling Fresh and Dry Weightsupporting
confidence: 88%
“…2). Similar results were found in the experiments of Hanan (2007), Singh and Usha (2003) and Shatpathy et al (2018). With the SFW value of 0.437 gm and SDW value 0.35 gm.…”
Section: Seedling Fresh and Dry Weightsupporting
confidence: 88%
“…Priming with SA at 100 mg L −1 enhanced emergence and early seedling growth in cucumber [ 151 ] and increased germination and productivity of Vicia faba [ 152 ] and sesame [ 153 ]. It has been reported that rice seeds primed with SA (100 ppm) had increased germination and accelerated seedling growth by ion absorption in PEG-induced water stress [ 131 ]. In addition, priming of rice seeds with SA enhanced tolerance to chilling stress by enhancing antioxidant enzyme activities and reducing oxidative damage [ 132 ].…”
Section: Commonly Used Pgrs In Seed Primingmentioning
confidence: 99%
“…An experiment was designed as twelve groups and was listed in Supplementary Table S1. The toxic levels of NaCl and PEG were chosen base on the study of Kurniasih et al (2016) and Shatpathy et al (2018), respectively. For determination of Nar application, the doses of Nar were selected as 0.1 mM and 0.4 mM according to Liu et al (2012).…”
Section: The Applications Of Stress and Naringenin And The Samplingmentioning
confidence: 99%